Aggravating Factors of Migraine among the Patients Attending Neuro-Medicine Outpatient Department at Two Selected Tertiary Level Hospital (Journal of Dhaka Medical College, 2018)
A descriptive cross-sectional type of study was conducted among the migraine patients attending the Neuromedicine department of Dhaka Medical College Hospital and Bangabandhu Sheikh Mujib Medical University to find out the aggravating factors of migraine in the year of 2006. Total number of respondents was 160. Among them 70% were female. Majority of the patients (46.25%) were aged between 21-30 years. Significant number of respondents (38.12%) was housewives; followed by 28.75% were student. The main aggravating factors so far identified in this study were sleep disturbance, bright light, noise and mental or physical stress. Other aggravating factors were various types of food, oral pill, relation with menstrual cycle. Respondents also stated more than one factor. Among the female respondents 39.8% practiced different types of contraceptive methods of which majority (82.05%) used OCP.J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 132-134